1980
DOI: 10.1902/jop.1980.51.10.578
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Clinical Evaluation of a 10% Strontium Chloride Dentifrice in Treatment of Dentin Hypersensitivity Following Periodontal Surgery

Abstract: Sixty adult patients were examined for dentin hypersensitivity prior to periodontal surgery. Stimuli used included mechanical, cold water and compressed air blasts. A subjective assessment of the degree of hypersensitivity for each stimulus was recorded. This presurgical examination revealed 249 hypersensitive areas among 60 subjects. Following surgery there was over a 100% increase in the pain (hypersensitivity) score. Desensitization with a 10% strontium chloride hexahydrate dentifrice was begun 1 week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 13 publications
(1 reference statement)
3
44
0
6
Order By: Relevance
“…A considerable placebo effect was found in the present study, corresponding to previous clinical trials of DH treatments that reported placebo effects of approximately 30%-40% depending on the parameter [22][23][24]. This phenomenon is a response to the intervention http://jpis.org itself and consists of complex physiologic and psychological manifestations of the patient's desire for symptom relief [25].…”
Section: Discussionsupporting
confidence: 78%
“…A considerable placebo effect was found in the present study, corresponding to previous clinical trials of DH treatments that reported placebo effects of approximately 30%-40% depending on the parameter [22][23][24]. This phenomenon is a response to the intervention http://jpis.org itself and consists of complex physiologic and psychological manifestations of the patient's desire for symptom relief [25].…”
Section: Discussionsupporting
confidence: 78%
“…In addition to differences in the number of teeth in each treatment group, classified according to Uchida's criteria, 14 after the treatment, were assessed the changes in level of sensitivity in both groups at baseline, immediately, at 15 days and at 30 days after treatment. The mean of the level of dentin hypersensitivity in each group for each time point was calculated; the level of dentin hypersensitivity at baseline was 1.93 AE 0.49 (mean AE S.D.).…”
Section: Resultsmentioning
confidence: 99%
“…Data were standardized by scoring the degree of sensitivity for each tooth according to the criteria proposed by Uchida et al, 14 which establishes four degrees for sensitivity depending on patient's response to stimulation (Table 1). This study was performed by one operator and one assessor responsible for the measurement of the sensitivity level of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of sensitivity to an evaporative stimulus was determined qualitatively using an air syringe of the dental unit, and a 1-sec cold air blast was blown 2 mm from the site to be tested. Sensitivity was scored according to the modified criteria proposed by Uchida et al, 23 which establishes four degrees of sensitivity, depending on the patient's response to stimulation (Table 1). Sensitivity was assessed before treatment, and 1 wk, and 1 mo, and 6 mo post-treatment by a single examiner who was blinded to the treatment given.…”
Section: Assessment Of Hypersensitivitymentioning
confidence: 99%